2020
DOI: 10.1380/ejssnt.2020.293
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Sulfonated Polyaniline Thin Film Grown on Different GaAs Substrates

Abstract: The paper describes the impact of the crystallographic orientation of an n-type GaAs substrate on the electrical properties of a sulfonated polyaniline (SPAN) thin film with a thickness of 120 nm grown on different n-type GaAs substrates orientation, which are (100), (311)A, and (311)B GaAs planes. Electrical characterization was performed by using current density-voltage (J−V) at room temperature and different temperatures (60−360 K). An ideality factor (n), a Schottky barrier height (Φb), and an activation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…120 nm grown on n-GaAs substrates with different orientations ((100), (311) A, and (311) B were studied by Jaqsi et al [112] They observed that the SPAN/(311) B n-GaAs device has better electrical performances than the SPAN/(100) and SPAN/(311) A n-GaAs devices. However, defects caused by the presence of an oxygen layer on GaAs substrates are the major factors limiting the performance of these devices.…”
Section: Device Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…120 nm grown on n-GaAs substrates with different orientations ((100), (311) A, and (311) B were studied by Jaqsi et al [112] They observed that the SPAN/(311) B n-GaAs device has better electrical performances than the SPAN/(100) and SPAN/(311) A n-GaAs devices. However, defects caused by the presence of an oxygen layer on GaAs substrates are the major factors limiting the performance of these devices.…”
Section: Device Structuresmentioning
confidence: 99%
“…However, if the highest occupied molecular orbital (HOMO) level of the HTL polymer is lower than the VBM of GaAs, the higher valence band maximum (VBM) of (111) B than that of (100) may lead to increased complexation due to blocked hole transport, as the band structure alignment shown in Figure 3g. More recently, the electrical characteristics of sulfonated polyaniline (SPAN) with a thickness of 120 nm grown on n‐GaAs substrates with different orientations ((100), (311) A, and (311) B were studied by Jaqsi et al [ 112 ] They observed that the SPAN/(311) B n‐GaAs device has better electrical performances than the SPAN/(100) and SPAN/(311) A n‐GaAs devices. However, defects caused by the presence of an oxygen layer on GaAs substrates are the major factors limiting the performance of these devices.…”
Section: Device Structure and Performancementioning
confidence: 99%